Construção, caracterização e otimização da magnetohipertermia de nanocarreadores multifuncionais fluorescentes: a importância da relaxação coletiva na geração de calor - Zufelato, Nícholas (2018)
In this work, we developed a multifunctional nanocarrier that has diagnostics and therapeutic applications in oncology, and evaluated the magnetothermal efficiency (SLP) properties in a comparative manner with respect to magnetic fluids. The nanocarrier consists of Mn-ferrite magnetic nanoparticles, a near-infrared fluorescent molecule IR-780, that are surface-coated with albumin proteins (BSA). The samples were characterized by dynamic light scattering (DLS), electron microscopy (TEM and MEV-FEG), vibrating sample magnetometer (VSM), fluorescence molecular tomography (FMT). FMT data proved the coupling of IR-780 to the protein allowing the fabrication of a magnetofluorescent nanostructure. Magnetic hyperthermia data as function of field amplitude (60-200 Oe) and frequency (170-990 kHz) were obtained for all samples containing the same magnetic particle volume fraction in the liquid carrier, but with distinct agregate sizes. The sizes were controlled by tuning the ionic force, and monitored experimentally using DLS. Magnetization curves revealed a (quasi-static) superparamagneticlike behavior, and was used to extract the particle concentration. The hyperthermia efficiency SLP of the magnetic fluids decreased increasing the hidrodynamic diameter. On the contrary, the nanocarrier showed a maximum of SLP, that can be optimized for hyperthermia and is more efficient than the ferrofluid. SLP data as function of frequency revealed a relaxation time of the order of 10-7 s and an equilibrium susceptibility lower than the Langevin value. A theoretical analysis of SLP at the linear responde regime was developed taking into account the dipolar interaction of nanoparticles organized in distinct arrangements. In magnetic fluids we considered a linear chain using the longitudinal configuration (anisotropy axis aligned), while for the nanocarriers we considered spherical agregates where the anisotropy axis of the nanoparticles are arranged randomly. The theoretical analysis indicate that the relaxation time cannot be explained by brownian relaxation or the Néel relaxation of single particle (even considering the dipolar effect). But instead, a mechanism of collective relaxation, mediated by dipolar interaction, is responsible for heat generation. It also indicates that only a fraction of agregates in the colloid is responsible for heating. In addition, the theoretical model revealed the existence of a transition from single particle relaxation to collective relaxation only if the dipolar interaction for the aggregate is higher than a critical value, which depends on material parameters, as for instance anisotropy field and saturation magnetization. Indeed, the model indicates that collective states are more easily achieved on soft magnets, and therefore suggests enhanced magnetothermal properties for this kind of materials.